Intraoral Repair of Dental Ceramics Using Er,Cr:YSGG Laser: Review - Noor Bader Hassan; Basima Mohammed Ali Hussein* (Iraqi Journal of Laser, 2023)
Introduction: All-ceramic crowns are widely used in prosthodontics and cosmetic dentistry due to their good esthetic and proper physical properties. Chipping of ceramic is one of the most common post-insertion complications, that can be fixed either extraoral or intraorally. The latter is time time-effective alternative, less traumatic, and low-cost. A newer objective method of laser is a surface modification of ceramics to increase surface roughness. The aim of this study is to provide a review of Er,Cr;YSGG (2960nm) in intraoral repair and shear bond strength (SBS). Method: A thorough search considering Google Scholar and PubMed published data and ten articles found who published between 2018 to 2022. Results:Because of the variation in the material composition of all ceramic crowns (feldspathic porcelain, zirconia, lithium dislocate, hybrid ceramics) different surface treatment methods are required for strong composite ceramic interphase. The effect of Er,Cr:YSGG on porcelain was minimal and lower than hydrofluoric acid, while for zirconia surface can be acceptable compared to no treatment. Conclusion: intraoral repair is an effective and cost-effective treatment that does not require multiple appointments. However, the success and durability of the restoration are dependent on technical and clinical experience and a superior understanding of material composition.Keywords: Intraoral repair, dental ceramics, ceramic chipping, Er,Cr:YSGG laser and shear bond strength (SBS).